Resistance paste and chip resistor

By using composite conductive phase MxTayBz and glass phase composed of rare earth metal or alkaline earth metal, combined with inorganic additives, the high cost of precious metal materials and environmental pollution in the resistive slurry is solved, and the resistance stability and TCR performance of the resistive layer are achieved. Improve and expand the application of resistance value range.

CN119181523APending Publication Date: 2024-12-24SUZHOU SANHUAN TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411430494.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The use of precious metal materials such as RuO2 in existing resistive slurries leads to high costs and environmental pollution, and the metal borides are oxidized and decomposed at high temperatures, resulting in the inability to meet the standards for resistance discreteness and TCR performance, which limits their resistance ranges in a wide range. Application.

Method used

The composite conductive phase MxTayBz composed of rare earth metal or alkaline earth metal is used to combine glass phase and inorganic additives to adjust the proportion and composition of the conductive phase, reduce high-temperature oxidation reaction, and improve resistance stability and TCR performance.

Benefits of technology

Effectively reduce the oxidation reaction of the conductive phase, improve the density and resistance stability of the resistor layer, expand the resistance range, improve TCR performance, and achieve better resistance discrete performance and wider resistance interval range. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005083518490000071
    Figure BDA0005083518490000071
  • Figure BDA0005083518490000081
    Figure BDA0005083518490000081
  • Figure BDA0005083518490000082
    Figure BDA0005083518490000082
Patent Text Reader

Abstract

The invention belongs to the field of electronic paste, and particularly discloses resistance paste and a chip resistor. The resistance paste comprises an inorganic component and an organic component, and the inorganic component comprises a conductive phase; the conductive phase comprises MxTayBz, x is greater than or equal to 1 and less than 50, y is greater than or equal to 1 and less than 50, z is greater than or equal to 2 and less than or equal to 296, and M is rare earth metal, alkaline earth metal or a combination of the rare earth metal and the alkaline earth metal. Compared with traditional metal borides such as lanthanum hexaboride and the like, the MxTayBz is adopted as the conductive phase of the resistance paste, and the MxTayBz has a more excellent temperature-sensitive characteristic, so that the self-oxidation reaction degree of the conductive phase during high-temperature sintering is greatly reduced, and the resistance paste has a wider resistance adjustable range under the condition of considering the resistance discrete performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electronic paste, and in particular relates to a resistor paste and a chip resistor. Background Art

[0002] As an important electronic component, chip resistors are widely used in thick film circuits, hybrid integrated circuits, electronic equipment and other fields. The resistance characteristics of thick film chip resistors mainly depend on the resistance layer, which is formed by printing thick film resistor paste on an insulating substrate and sintering it. The conductive phase in the resistor paste is usually made of RuO2, Pb2Ru2O 6.5 、Bi2Ru2O 6.5 Precious metal materials mainly containing Ru, such as lanthanum boride, are expensive and contain lead, which causes great environmental pollution. At present, in order to reduce costs and reduce environmental pollution risks, it is expected to use metal borides such as lanthanum boride as the conductive phase material of resistor paste. However, when adjusting the resistance value of such resistor paste by adjusting the content of conductive phase and glass phase, since metal borides are easily oxidized and decomposed at high temperature to produce gas, and the degree of reaction increases with temperature, it is easy to have electrical properties such as resistance, resistance discreteness and TCR (temperature coefficient of resistance) performance that cannot meet the standards. This seriously limits the application of metal borides in resistor pastes with a wide range of different resistance segments. Summary of the invention

[0003] In order to overcome at least one technical problem existing in the above-mentioned prior art, one of the objectives of the present invention is to provide a resistor paste.

[0004] A second object of the present invention is to provide a chip resistor.

[0005] A third object of the present invention is to provide application of the above resistor paste in electronic components.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] The first aspect of the present invention provides a resistor paste, comprising an inorganic component and an organic component, wherein the inorganic component comprises a conductive phase; the conductive phase comprises M x Ta y B z , wherein 1≤x<50, 1≤y<50, 2≤z≤296, and M is a rare earth metal, an alkaline earth metal, or a combination of the two.

[0008] The resistor paste of the present invention adopts M x Ta y B zAs a conductive phase, it has excellent temperature sensitivity, which greatly reduces the degree of self-oxidation reaction of the conductive phase during high-temperature sintering, reduces the side reactions of the conductive phase during the sintering process, and ensures that the resistor layer has good density and resistance stability after sintering, thereby effectively improving the resistance discreteness performance of the resistor layer.

[0009] In the present invention, x Ta y B z In the range of x, 1≤x<50, for example, x can be selected from 1, 1.1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 19.7, 20, 21, 22, 23, 23.7, 24, 25, 26, 27, 27.9, 28, 29, 30, 31, 32, 33 , 34, 34.5, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 45.3, 46, 47, 47.3, 48, 48.7, 49, 49.4, 49.8; preferably, 1.3≤x≤45; further preferably, 2≤x≤35; further preferably; 3≤x≤20; more preferably, 3≤x≤11.

[0010] In the present invention, x Ta y B z , the value range of y is: 1≤y<50, for example, y can be selected from 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.7, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 19.7, 20, 21, 22, 23, 23.7, 24, 25, 26, 27, 27.9, 28, 29, 30, 31, 32, 33, 34, 34.5, 35, 36, 36.7, 37, 38, 39, 40, 41, 42, 43, 44, 45, 45.3, 46, 47, 47.3, 48, 48.7, 49, 49.4, 49.8; preferably, 1.5≤y≤45; further preferably, 2≤y≤30; still further preferably, 3≤y≤20; more preferably, 3≤y≤10.

[0011] In the present invention, x Ta y B z, the value range of z is: 2≤z≤296, for example, z can be selected from 2, 4, 6, 8, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 295, 296; preferably, 2.5≤z≤240; further preferably, 10≤z≤200; further preferably, 18≤z≤160; further preferably, 20≤z≤100; more preferably, 20≤z≤65.

[0012] In the present invention, M is selected from at least one of lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), lutetium (Lu), scandium (Sc), yttrium (Y), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), and radium (Ra); more preferably, M is selected from at least one of La, Ce, Y, Ca, Ba, and Sr.

[0013] Preferably, the inorganic component includes the following components in mass percentage: 2.5-56% conductive phase, 44-97% glass phase, and 0-10% inorganic additives.

[0014] Preferably, the glass phase includes the following components in mass percentage: 22-65% SiO2, 2-25% Al2O3, 5-40% B2O3, 2-15% CaO, 0-50% Ta2O5, 0-10% MgO, 0-10% SrO, 0-10% TiO, 0-10% ZnO, 0-10% Na2O, and 0-10% K2O.

[0015] Preferably, the inorganic additive is selected from at least one of Co2O3, MnO2, Al2O3, ZrO2 and graphite.

[0016] Preferably, the organic component includes the following components in mass percentage: 2-15% resin, 75-95% organic solvent, and 0.1-18% organic additive.

[0017] In the present invention, the mass percentage of the resin is 2-15%, for example, can be selected from 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%.

[0018] Preferably, the resin is selected from at least one of methyl cellulose, ethyl cellulose, acrylic resin, epoxy resin, alkyd resin, terpene resin and modified rosin.

[0019] In the present invention, the mass percentage of the organic solvent is 75-95%, for example, can be selected from 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%.

[0020] Preferably, the organic solvent is selected from at least one of terpineol, butyl carbitol, butyl carbitol acetate, diethylene glycol dibutyl ether, turpentine, isobornyl acetate, dibutyl phthalate, and alcohol ester dodecahydrate.

[0021] In the present invention, the mass percentage of organic additives is 0.1-18%, for example, can be selected from 0.1%, 0.3%, 0.5%, 0.8%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%.

[0022] Preferably, the organic additive is selected from at least one of sodium lauryl sulfate, methyl amyl alcohol, aminopropylamine dioleate, oleylamino oleate, and lecithin.

[0023] Preferably, M in the conductive phase x Ta y B z The mass ratio of the inorganic additive is a, 2≤a≤50, for example, a can be selected from 2, 3, 3.2, 3.9, 4, 4.32, 5, 5.1, 5.2, 5.3, 5.6, 5.9, 6, 6.8, 7, 7.5, 8, 9, 9.5, 9.8, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 20.7, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 48.9, 49, 50; In the practical application of resistor paste, it is expected to have excellent TCR performance, and the ideal situation is that the absolute value of TCR tends to zero. However, the composite conductive material M x Ta y B zWhen used as a conductive phase of a resistor paste, although the resistance discreteness performance can be greatly improved, the TCR will have a certain degree of positive offset (when the resistor paste is in the low resistance range) or negative offset (when the resistor paste is in the high resistance range), that is, the absolute value of the TCR is far away from the ideal zero value, resulting in a decrease in TCR performance. The present invention can effectively suppress the offset of TCR by adding inorganic additives to the resistor paste to adjust TCR. The inventor has found through a large number of experiments that when a is in the range of 2 to 50, the resistance discreteness and TCR performance of the resistor paste are better. When a < 2, the composite conductive material M x Ta y B z The content is low, the resistance discrete performance becomes worse, and at the same time, the content of inorganic additives is high, resulting in a reverse shift of TCR and poor TCR adjustment effect; when a>50, the composite conductive material M x Ta y B z Excessive, low content of inorganic additives, inhibiting the composite conductive material M x Ta y B z The effect of the TCR offset problem is worsened. Further preferably, 3≤a≤40; still further preferably, 5≤a≤30; and more preferably, 7≤a≤15.

[0024] Preferably, the conductive phase further comprises an auxiliary conductive material; x Ta y B z The mass ratio of the auxiliary conductive material to the auxiliary conductive material is b, 3.25≤b<50, for example, b can be selected from 3.25, 3.3, 3.9, 4, 4.32, 5, 5.1, 5.2, 5.3, 5.6, 5.9, 6, 6.6, 6.8, 7, 7.5, 8, 9, 9.5, 9.8, 10, 11, 12, 13, 14, 15, 16, 17, 18, 18.1, 18.4, 19, 19.2, 20, 20.7, 21, 21.6, 22, 23, 24, 25, 25.3, 26, 27, 28, 29, 30, 31, 32, 33, 34, 34.5, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 48.9, 49, 50; the addition of auxiliary conductive materials can further expand the range of M x Ta y B z In addition, when the b value meets the above range, during the sintering process of the resistor paste, the auxiliary conductive material is oxidized into oxides such as copper oxide and nickel oxide in the air, and M x Ta y B zThe degree of redox reaction with these oxides is lower, and the resistance is more stable, so that the resistor paste has both excellent resistance discreteness performance and a wider resistance range, and is more widely used. Further preferably, 3.5≤b≤40; further preferably, 4.5≤b≤30; more preferably, 7≤b≤15.

[0025] Preferably, the auxiliary conductive material is selected from at least one of copper, nickel or copper-nickel alloy.

[0026] Preferably, when 3.25≤b<20, 2≤a<8.

[0027] Preferably, when 20≤b<50, 8≤a≤50.

[0028] The inventors have found through a large number of experiments that when 3.25≤b<20, compared with the case of 2≤a<8, if a<2 or a≥8, the resistance dispersion performance of the resistor paste decreases; when 20≤b<50, compared with the case of 8≤a≤50, if a<8, the resistance dispersion performance of the resistor paste decreases, and when a>50, the TCR performance deteriorates. Therefore, when the values ​​of a and b meet the above conditions, the resistor paste has better resistance dispersion performance and TCR performance.

[0029] Preferably, the M x Ta y B z 35,36,37,38,39,39.42,40,41,42,43,44,44.9,45. When the ratio of x to y is 0.5 to 45, the composite conductive material M x Ta y B z The temperature sensitivity of the composite conductive material M is better when sintered at high temperature. x Ta y B z The degree of self-oxidation reaction is lower, so that the resistor layer made of the resistor paste has a more excellent resistance discrete performance; further preferably, the M x Ta y B zThe ratio of x to y is 0.7 to 40; further preferably, the M x Ta y B z The ratio of x to y is 1 to 35; more preferably, the M x Ta y B z The ratio of x to y is 1.5 to 28; further preferably, the M x Ta y B z The ratio of x to y is 2 to 21; more preferably, the M x Ta y B z The ratio of x to y is 2 to 15.

[0030] Preferably, the mass percentage of the inorganic component in the resistor paste is 40-80%; further preferably, the mass percentage of the inorganic component in the resistor paste is 40-80%, and the mass percentage of the organic component is 20-60%.

[0031] In the present invention, the mass percentage of inorganic component is 40-80%, for example, can be selected from 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%.

[0032] In the present invention, the mass percentage of organic component is 20-60%, for example, can be selected from 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48%, 50%, 52%, 54%, 56%, 58%, 60%.

[0033] Preferably, the average grain size of the auxiliary conductive material is 0.1-10 μm, for example, can be selected from 0.1 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, and 10 μm.

[0034] Preferably, the M x Ta y B zThe average grain size is 0.1-10 μm, for example, can be selected from 0.1 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, and 10 μm.

[0035] Preferably, the average particle size of the glass phase is 0.5-10 μm, for example, can be selected from 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, and 10 μm.

[0036] Preferably, the average particle size of the inorganic additive is 0.1 to 5 μm, for example, can be selected from 0.1 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, and 5 μm.

[0037] Preferably, the resistor paste is prepared by a preparation method comprising the following steps:

[0038] The resin, solvent and organic additive are heated and mixed to obtain an organic carrier;

[0039] Mixing the conductive phase, the glass phase and the inorganic additive to obtain an inorganic mixed powder;

[0040] The organic carrier and the inorganic mixed powder are premixed and then rolled to obtain the resistor paste.

[0041] Preferably, the heating temperature is 60-120°C.

[0042] Preferably, the rotation speed of the mixing step is 10 to 480 rpm.

[0043] Preferably, the rotation speed of the premixing step is 60 to 720 rpm.

[0044] Preferably, the rolling step is performed on a three-roll rolling mill.

[0045] Preferably, the M x Ta y B z It is prepared by a preparation method comprising the following steps:

[0046] The boride of M metal is ground and mixed with Ta2O5, and then sintered to obtain the product.

[0047] Preferably, the grinding and mixing step is performed by ball milling.

[0048] Preferably, the ball milling time is 10 to 20 hours.

[0049] Preferably, the ball milling frequency is 3.8 to 10.8 Hz.

[0050] Preferably, the ball-to-material ratio of the ball milling step is 1:10 to 1:25; the ball-to-material ratio refers to the ratio of the mass of the grinding balls to the total mass of the boride of the M metal and Ta2O5.

[0051] Preferably, the sintering temperature is 500-850°C.

[0052] Preferably, the sintering time is 10 to 60 minutes.

[0053] The second aspect of the present invention provides a chip resistor, comprising a resistor layer; the resistor layer is made of the resistor paste described in the first aspect of the present invention.

[0054] The third aspect of the present invention provides use of the resistor paste described in the first aspect of the present invention in electronic components.

[0055] Preferably, the electronic components include thick film circuits, hybrid integrated circuits, electronic devices, and resistors.

[0056] The beneficial effects of the present invention are as follows: x Ta y B z As the conductive phase of resistor paste, M x Ta y B z It has better temperature sensitivity and greatly reduces the degree of self-oxidation reaction of the conductive phase during high-temperature sintering, so that the resistor paste has a wider adjustable resistance range while taking into account the discrete resistance performance. DETAILED DESCRIPTION

[0057] The specific implementation of the present invention is further described in detail below in conjunction with examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially.

[0058] The raw material information used in the examples and comparative examples of the present invention is as follows:

[0059] Composite conductive material M x Ta y B z The average grain size is 1.5 μm;

[0060] The average grain size of the auxiliary conductive material is 0.5 μm;

[0061] The average particle size of the glass powder is 1.5 μm;

[0062] The average particle size of the inorganic additive is 2 μm.

[0063] The types and contents of the conductive phase (composite conductive material MxTayBz / mixed conductive material, auxiliary conductive material) and inorganic additives in the embodiments and comparative examples of the present invention can be obtained by X-ray photoelectron spectroscopy (XRF) testing; the composite conductive material M x Ta y B z The types and contents of each element in the sample can be obtained by transmission electron microscopy (TEM) testing.

[0064] Example 1

[0065] This example provides a resistor paste, including an inorganic component and an organic component, the formula of the inorganic component is shown in Table 1, and the formula of the organic component is shown in Table 2;

[0066] Among them, the mass ratio of inorganic components to organic components is 7:3;

[0067] Taking the total mass percentage of the inorganic component as 100%, the inorganic component is composed of the following mass percentages: 15% of the composite conductive material M x Ta y B z , 0.5% auxiliary conductive material, 81.5% glass phase, 3% inorganic additives;

[0068] Composite conductive material M x Ta y B z The mass ratio of the inorganic additive is a, a is 5; the composite conductive material M x Ta y B z The mass ratio of the composite conductive material M to the auxiliary conductive material is b, where b is 30; x Ta y B z La3Ta2B 22 , the ratio of x to y is 1.5; the mass ratio of the inorganic component to the organic component, the ratio of x to y, and the values ​​of a and b are specifically shown in Table 3; the auxiliary conductive material is a copper-nickel alloy; the inorganic additive is Co2O3;

[0069] The type of the glass phase is G7. Taking the total mass percentage of the glass phase as 100%, the glass phase is composed of the following components in mass percentage: 25% SiO2, 20% Al2O3, 40% B2O3, 12% CaO, 0.5% SrO, 0.5% TiO, 0.5% ZnO, 1% Na2O, and 0.5% K2O. The formula of the glass phase is shown in Table 4.

[0070] Taking the total mass percentage of the organic components as 100%, the organic components are composed of the following components in mass percentage: 6.2% of resin, 2.5% of organic additives, and 91.3% of solvent; the resin is ethyl cellulose; the organic additive is lecithin; and the solvent is pinene alcohol.

[0071] Embodiments 2 to 30

[0072] Referring to Example 1, the formula of the inorganic component of the resistor paste in Examples 2 to 30 is shown in Table 1, the formula of the organic component is shown in Table 2, the mass ratio of the inorganic component to the organic component, the ratio of x to y, the composite conductive material M x Ta y B z and the mass ratio of inorganic additives a, composite conductive material M x Ta y B z The specific value of the mass ratio b of the auxiliary conductive material is shown in Table 3; the formula of the glass phase is shown in Table 4.

[0073] Embodiments 1 to 30 of the present invention all use composite conductive material M x Ta y B z For comparison, the present invention sets Comparative Examples 1 to 5, in which a mixed conductive material of metal boride and Ta2O5 is used to replace the composite conductive material M in the embodiment. x Ta y B z , as follows:

[0074] Comparative Example 1

[0075] The difference between the resistor paste in this example and that in Example 14 is that this example uses a mixed conductive material of LaB6 and Ta2O5 with a mass ratio of 1:1 instead of La3Ta2B in Example 14. 22 The specific formula of the mixed conductive material is shown in Table 5.

[0076] Comparative Example 2

[0077] The difference between the resistor paste in this example and that in Example 8 is that this example uses a mixed conductive material of LaB6 and Ta2O5 with a mass ratio of 0.5:1 to replace the La in Example 8. 15 Ta 49 B 189 The specific formula of the mixed conductive material is shown in Table 5.

[0078] Comparative Example 3

[0079] The difference between the resistor paste in this example and that in Example 10 is that this example uses a mixed conductive material of LaB6 and Ta2O5 with a mass ratio of 6.6:1 instead of La in Example 10. 19.7 Ta 1.1 B 25 The specific formula of the mixed conductive material is shown in Table 5.

[0080] Comparative Example 4

[0081] The difference between the resistor paste in this example and Example 24 is that this example uses a mixed conductive material of SrB6 and Ta2O5 with a mass ratio of 10.8:1 instead of Sr in Example 24. 49.4 Ta 1.1 B 264 The specific formula of the mixed conductive material is shown in Table 5.

[0082] Comparative Example 5

[0083] The difference between the resistor paste in this example and Example 21 is that this example uses a mixed conductive material of YB6 and Ta2O5 with a mass ratio of 5:1 instead of Y in Example 21. 23.7 Ta 1.5 B 22 The specific formula of the mixed conductive material is shown in Table 5.

[0084] Table 1 Formulas of inorganic components in Examples 1 to 30 and Comparative Examples 1 to 5

[0085]

[0086]

[0087] Table 2 Formulation of organic components in Examples 1 to 30 and Comparative Examples 1 to 5

[0088]

[0089]

[0090] Table 3 Numerical values ​​of parameters in Examples 1 to 30 and Comparative Examples 1 to 5

[0091]

[0092]

[0093] Table 4 Formulation of glass phase

[0094]

[0095]

[0096] Table 5 Formulas of mixed conductive materials in Comparative Examples 1 to 5

[0097]

[0098] The resistor pastes in Examples 1 to 30 of the present invention and Comparative Examples 1 to 5 can be prepared by the following preparation method:

[0099] a. Dissolve the resin in the solvent at a heating temperature of 80°C, a straight-blade paddle stirring method, and a stirring speed of 280 rpm, then add an organic additive, filter and cool to obtain a viscous colloidal organic carrier; x Ta y B z / mixed conductive material and auxiliary conductive material), glass phase, and inorganic additives are pre-mixed and dispersed to obtain an inorganic mixed powder;

[0100] b. Add the inorganic mixed powder into the organic carrier in a certain proportion, stir (stirring method is straight blade paddle type, speed is 580 rpm) for premixing, and then fully disperse it evenly through a three-roll mill to obtain a resistor slurry.

[0101] The composite conductive material M in Examples 1 to 30 of the present invention x Ta y B z The method is prepared by a preparation method comprising the following steps:

[0102] a. Ball mill the metal boride and Ta2O5 for 10 to 20 hours at a ball milling frequency of 3.8 to 10.8 Hz and a ball-to-material ratio (the ratio of the mass of the grinding ball to the total mass of the metal boride and Ta2O5) of 1:10 to 1:25;

[0103] b. Sintering the ball-milled powder in a muffle furnace at a sintering temperature of 500 to 850°C for 10 to 60 minutes;

[0104] c. By adjusting the preparation process parameters and the ratio of metal boride to Ta2O5 addition, different composite conductive materials M in Examples 1 to 30 can be obtained. x Ta y B z ; Composite conductive material M in Examples 1 to 30 x Ta y B z The preparation process parameters and raw material ratios are shown in Table 6 below.

[0105] Table 6 Composite conductive material M x Ta y B z Process parameters and raw material ratio

[0106]

[0107] Performance Testing

[0108] The various properties of the resistor pastes in Examples 1 to 30 and Comparative Examples 1 to 5 were tested respectively, and the specific testing methods were as follows:

[0109] (1) Sample preparation:

[0110] The resistance layer size of 1206 chip resistor specifications (effective size is 1mm*1.32mm, sintered film thickness is 6-12μm) is used as the test sample. The thick film resistor paste is printed on the alumina substrate by screen printing process. After sintering at 850℃ in air atmosphere, the test sample is obtained. The number of test samples is n.

[0111] (2) Resistance R and resistance discreteness SD test:

[0112] Use a resistance meter to test the resistance value Ri of each sample and calculate the average resistance value of all tested samples The resistance dispersion coefficient is calculated by the formula When RSD≤6%, it is a qualified product. In the present invention, n is 500.

[0113] (3) TCR test:

[0114] The test samples were kept at constant temperatures of 125°C, 25°C, and -55°C for 10 min, the resistance of the samples was tested, and the TCR was calculated.

[0115]

[0116] CTCR: low temperature (cold) TCR, T = -55 ° C;

[0117] HTCR: high temperature (hot) TCR, T = 125 ° C;

[0118] When CTCR and HTCR are within ±100ppm / ℃, the performance is better.

[0119] The various properties of the resistor pastes in Examples 1 to 30 and Comparative Examples 1 to 5 measured according to the above test method are shown in Table 7 below.

[0120] Table 7 Properties of the resistor pastes in Examples 1 to 30 and Comparative Examples 1 to 5

[0121]

[0122]

[0123] As shown in Table 7, compared with the mixed conductive material (i.e., the mixture of metal boride and Ta2O5) used in Comparative Examples 1 to 5, the resistor pastes in Examples 1 to 30 all use the composite conductive material M x Ta y B z , which can effectively improve the resistance dispersion performance of the resistor layer made of the resistor paste, so that the resistance dispersion performance does not exceed 6%. The composite conductive material M used in the resistor paste in Example 2, Example 4, Example 8, Example 13, and Example 17 x Ta y B z In the embodiment, the ratio of x to y does not meet the range of 0.5 to 45, and the resistance dispersion performance of the resistor layer made of the resistor paste is slightly worse than that of other embodiments, but still meets the requirements.

[0124] When metal borides such as LaB6, SrB6, CeB6, CaB6, and YB6 are used as conductive phase materials for resistor pastes, metal borides have poor temperature sensitivity and are easily oxidized and decomposed at high temperatures to produce gas, which reduces the density of the resistor layer after sintering and has poor resistance stability. Compared with traditional metal borides such as lanthanum hexaboride, the present invention adopts a composite conductive material M x Ta y B z As the conductive phase of the resistor paste, the composite conductive material M x Ta y B z It has better temperature sensitivity and greatly reduces the degree of self-oxidation reaction of the conductive phase during high-temperature sintering, so that the resistor paste has a wider adjustable resistance range while taking into account the discrete resistance performance.

[0125] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A resistor paste comprising an inorganic component and an organic component, characterized in that: The inorganic component includes a conductive phase; the conductive phase includes M x Ta y B z , wherein 1≤x<50, 1≤y<50, 2≤z≤296, and M is a rare earth metal, an alkaline earth metal, or a combination of the two.

2. The resistor paste according to claim 1, characterized in that: The inorganic component comprises the following components in mass percentage: 2.5-56% of conductive phase, 44-97% of glass phase, and 0-10% of inorganic additives.

3. The resistor paste according to claim 2, characterized in that: The glass phase includes the following components in mass percentage: 22-65% SiO2, 2-25% Al2O3, 5-40% B2O3, 2-15% CaO, 0-50% Ta2O5, 0-10% MgO, 0-10% SrO, 0-10% TiO, 0-10% ZnO, 0-10% Na2O, 0-10% K2O; And / or, the inorganic additive is selected from at least one of Co2O3, MnO2, Al2O3, ZrO2, and graphite; And / or, the organic component includes the following components in percentage by mass: 2-15% resin, 75-95% organic solvent, and 0.1-18% organic additive.

4. The resistor paste according to claim 2, characterized in that: The M in the conductive phase x Ta y B z The mass ratio with the inorganic additive is a, 2≤a≤50; And / or, the conductive phase further comprises an auxiliary conductive material; the auxiliary conductive material is selected from at least one of copper, nickel or copper-nickel alloy; the M x Ta y B z The mass ratio of the auxiliary conductive material to the auxiliary conductive material is b, 3.25≤b<50.

5. The resistor paste according to claim 4, characterized in that: When 3.25≤b<20, 2≤a<8; Or, when 20≤b<50, 8≤a≤50.

6. The resistor paste according to claim 1, characterized in that: The M x Ta y B z The ratio of x to y is 0.5 to 45.

7. The resistor paste according to claim 1, characterized in that: The mass percentage of the inorganic component in the resistor paste is 40-80%.

8. The resistor paste according to claim 2, characterized in that: The M x Ta y B z The average grain size is 0.1 to 10 μm; and / or, the average particle size of the glass phase is 0.5 to 10 μm; And / or, the average particle size of the inorganic additive is 0.1 to 5 μm.

9. A chip resistor, characterized in that: It comprises a resistor layer; the resistor layer is made of the resistor paste according to any one of claims 1 to 8.

10. Use of the resistor paste according to any one of claims 1 to 8 in electronic components.